AMERICAN - BASED PRONUNCIATION STANDARTS OF ENGLISH ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2024)
This article explores the pronunciation standards of American English, focusing on the evolution and key features that distinguish it from other varieties of English, such as British English. It delves into the historical roots of American English pronunciation, highlighting the influences of European settlers and key linguistic reforms, particularly those introduced by Noah Webster. The article emphasizes the defining characteristics of American English pronunciation, such as rhoticity (the clear pronunciation of the "r" sound), vowel shifts, nasalization, and distinctive patterns of stress and intonation. It also discusses General American English as the standardized pronunciation used in formal settings, while acknowledging the rich diversity of regional accents across the U.S. In conclusion, the article underscores the importance of understanding American pronunciation standards for effective communication, while celebrating the diversity of regional speech patterns that enrich the language.